Information Technology for Clinical, Translational and Comparative Effectiveness Research - Daniel, C.; Choquet, R. (Yearbook of Medical Informatics, 2013)
Objectives: To summarize advances of excellent current research in the new emerging field of Clinical Research Informatics.Method: Synopsis of four key articles selected for the IMIA Yearbook 2013. The selection was performed by querying PubMed and Web of Science with predefined keywords. From the original set of 590 papers, a first subset of 461 articles which was in the scope of Clinical Research Informatics was refined into a second subset of 79 relevant articles from which 15 articles were retained for peer-review.Results: The four selected articles exemplify current research efforts conducted in the areas of data representation and management in clinical trials, secondary use of EHR data for clinical research, information technology platforms for translational and comparative effectiveness research and implementation of privacy control.Conclusions: The selected articles not only illustrate how innovative information technology supports classically organized randomized controlled trials but also demonstrate that the long promised benefits of electronic health care data for research are becoming a reality through concrete platforms and projects.
Keywords: Medical informatics; Biomedical Research; Epidemiologic Study Characteristics as Topic; Evaluation Studies as Topic; Patient Selection